Generating visual concept maps based on image annotation and commonsense knowledge acquisition - Alireza, Kashian (2009)
Representing a domain of knowledge in a computer is a highly complex task that involves the knowledge representation itself, domain-specific particularities, and problem in extracting knowledge from people, among others. This problem becomes more complex when knowledge is dynamically introduced by a user who is not necessarily a computer expert. According to Novak[1], a formalism named "concept map" is extremely powerful for human education and communication. These simple nets would be auxiliary to computer, more specifically in tasks where structural domain knowledge is important. Concept maps are also useful for reasoning, information retrieval and they even can be used for knowledge simulation and learning purposes.